Contractualization in the Higher Educational Institutions (HEIs) in Cebu - Louiechi Von R. Mendoza (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study made use of qualitative design as a method for describing the observance of contractualization in selected Higher Educational Institutions in Cebu. The researcher utilized narratives as well as quantitative data gathered through interviews. Interviews are made with persons directly involved with the practice of contractualization in the administrative and academic offices of the selected Higher Educational Institutions. There are a total of twelve (12) key informants for the study. The key informants are composed of the following: four guest lecturers, four agency-based administrative staff, and four janitorial or maintenance staff. The gathered data is validated by citing related studies and other references.